2014
DOI: 10.1080/10236244.2013.868075
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prolonged food deprivation on the covering behavior of the sea urchinsGlyptocidaris crenularisandStrongylocentrotus intermedius

Abstract: In this study, we investigated effects of 24 weeks of food deprivation on covering behavior of Glyptocidaris crenularis and Strongylocentrotus intermedius. Neither G. crenularis nor S. intermedius significantly reduced covering behavior during both short-and long-term food deprivation. However, G. crenularis and S. intermedius had significantly different behavioral patterns over the 24 weeks. Covering behavior of G. crenularis greatly increased from the first to the second week, with decreasing reaction time a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…This result is consistent with our previous fi nding that starvation does not signifi cantly aff ect covering behavior of G . crenularis (Zhao et al, 2014). Contrary to righting behavior, we found that covering behavior was not signifi cantly correlated with body size of G .…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…This result is consistent with our previous fi nding that starvation does not signifi cantly aff ect covering behavior of G . crenularis (Zhao et al, 2014). Contrary to righting behavior, we found that covering behavior was not signifi cantly correlated with body size of G .…”
Section: Discussioncontrasting
confidence: 81%
“…Glyptocidaris crenularis can be distinguished by their fl at test and long spines. They live on rocky and sandy bottoms at depths of 5-150 m. According to our laboratory observations and a previous study (Zhao et al, 2014), G . crenularis has obvious covering and righting behaviors.…”
Section: Introductionmentioning
confidence: 98%
“…Glyptocidaris urchins show increased cryptic behavior in the lab when sand is poured into their environment, which suggests that these urchins cover themselves to shield from floating debris [13]. Another study noted that starved Glyptocidaris urchins continue to cover themselves, which suggests that the behavior is important for survival, as it persists even when the energetic cost of maintaining it is fairly high [32].…”
Section: Covering As Mechanical Protectionmentioning
confidence: 97%
“…Glyptocidaridae (Zhao, Zhou, et al, 2014) personal observations. We make no claim that this list is exhaustive.…”
Section: Glyptocidaris Crenularismentioning
confidence: 99%